Job Satisfaction Among Private and Public College/Campus Teachers of Madhesh Pradesh in Nepal - Shrestha, Binay; Agrawal, Neha (Archives of Business Research, 2024)
Job satisfaction among the teachers has been found as a fundamental element influencing the performance of the organisation. The purpose of this study was to examine the Job satisfaction among private and public college/campus teachers of Madhesh Pradesh in Nepal. The current research work is based on Herzberg’s Two Factor Theory of Motivation and Job satisfaction. The variables included in the study are independent variables of intrinsic factors i.e., Job Itself, Promotion & recognition and extrinsic factors i.e., Colleagues, Pay &benefits, Students and Physical environment with Job satisfaction as a dependent variable. A descriptive and analytical research design using questionnaire method on 5-point Likert scale was used to collect and analyse the data. The study was conducted with the sample size of 250 teachers teaching in private/public campuses of Madhesh Pradesh in Nepal. The data were analysed through the use of descriptive statistics, correlation, multiple regression analysis and t-test using SPSS software. The results of the study infer that both the extrinsic and intrinsic factors are important in determining the job satisfaction level of teachers working in higher education sector of Madhesh Pradesh in Nepal. Few of the extrinsic factors like only pay & benefits and physical environment are not found to have the significant influence on job satisfaction level of teachers.